DISTRIBUTION OF URBAN HEAT ISLAND INDEX IN THE SURABAYA, YOGYAKARTA, AND BANDUNG USING REMOTE SENSING - Callista Fabiola Candraningtyas; Hashfi Hawali Abdul Matin; Sapta Suhardono; Yoyon Wahyono (Universitas Sebelas Maret (UNS), 2025)
Climate change is a global issue as it drives global warming and heightens the impact of greenhouse gases. In the past decade, the Urban Heat Island (UHI) phenomenon has become a growing concern in major cities due to urbanization and development. This study aims to analyze the distribution and relationship between changes in Land Surface Temperature (LST), Normalized Difference Vegetation Index (NDVI), and Normalized Difference Built-up Index (NDBI) with UHI changes in Surabaya, Yogyakarta, and Bandung, and propose mitigation strategies. The descriptive quantitative approach is used in the research to explain the calculated area and percentage of NDVI, NDBI, LST, and UHI. Geographic Information System (GIS) technology, specifically ArcGIS 10.8, was utilized to process Landsat imagery data from 1994 and 2024, enabling spatial analysis and visualization of urban heat distribution and land use changes. Simple correlation analysis was also carried out to examine the relationship between LST and NDVI, as well as LST and NDBI. The analysis shows that NDVI decreased, while NDBI, LST, and UHI increased over the 30 years in all three cities. LST and NDVI have a strong inverse relationship, where increasing LST correlates with decreasing NDVI. NDBI shows a positive relationship with LST, meaning more built-up areas lead to higher LST and UHI. Mitigation strategies include expanding green spaces, adopting green building technologies, and utilizing renewable energy.